PARTISIPASI KONTRAKTOR DI KOTA DENPASAR DALAM LELANG PENGADAAN BARANG DAN JASA PEMERINTAH SECARA ELEKTRONIK - Suciptapura, I Md; Adnyana Putera, I G. A.; Nadiasa, Mayun (JURNAL SPEKTRAN, 2013)
Electronic auction is an activity to provide goods / services by creating fair competition among providers of goods / services by complying with the principle of utilizing the facilities of communication and information technology. The purpose of this study was to determine the participation and acquisition of project contracting in the electronic auction to determine the relationship between the qualifications of the contractor, the contractor characteristics and conditions of participation in the electronic auction and acquisition projects, and to determine the factors that affect government contractors to participate in the auction. The study was conducted in the city of Denpasar. Methods of data collection using questionnaires and interviews addressed to contractors who have experience in the electronic auction. The method used is descriptive analysis, product moment correlation, regression and factor analysis using SPSS. The results showed that the characteristics of contractor availability factor of human resources project that comes with a certificate of availability of skilled experts and heavy equipment together to increase participation in the auction and acquisition projects. Lack of equipment auctions and bad internet connection is a factor that can degrade electronic participation and acquisition projects in the electronic auction. Factors affecting contractors to participate in the auction consists of 9 major factors such as: human resources and corporate confidence, and the location of the project, the contract system and auction system, Level Competition auction, capital and time, experience, government policies and economic conditions, The type and amount of equipment, construction market conditions
Keywords: electronic auction, contractor qualifications and characteristics, factors auction participation